2020
DOI: 10.3390/ijms21041477
|View full text |Cite
|
Sign up to set email alerts
|

Sex/Gender-Specific Imbalance in CVD: Could Physical Activity Help to Improve Clinical Outcome Targeting CVD Molecular Mechanisms in Women?

Abstract: In the last two decades, new insights have been gained regarding sex/gender-related differences in cardiovascular disease (CVD). CVD represents the leading cause of death worldwide in both men and women, accounting for at least one-third of all deaths in women and half of deaths in women over 50 years in developing countries. Important sex-related differences in prevalence, presentation, management, and outcomes of different CVDs have been recently discovered, demonstrating sex/gender-specific pathophysiologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 120 publications
0
16
0
Order By: Relevance
“…In the last two decades, new evidence demonstrated sex/gender-related differences in CVD, highlighting the role of sex hormones in protecting women from CVDs and providing an advantage over men that is lost when women reach the menopause stage. This hormonal-dependent shift of sex-related CVD risk affects overall CVD epidemiology, particularly in light of the increasing trend of population aging [ 2 ]. Moreover, according to Plugge and coworkers [ 46 ], women in lower-income groups have higher CVD risk and report higher rates of cigarette smoking, lower consumption of fruit and vegetables, higher fat diet, and less total PA than women in higher-income or social groups.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the last two decades, new evidence demonstrated sex/gender-related differences in CVD, highlighting the role of sex hormones in protecting women from CVDs and providing an advantage over men that is lost when women reach the menopause stage. This hormonal-dependent shift of sex-related CVD risk affects overall CVD epidemiology, particularly in light of the increasing trend of population aging [ 2 ]. Moreover, according to Plugge and coworkers [ 46 ], women in lower-income groups have higher CVD risk and report higher rates of cigarette smoking, lower consumption of fruit and vegetables, higher fat diet, and less total PA than women in higher-income or social groups.…”
Section: Resultsmentioning
confidence: 99%
“…In 2016, 17.9 million people died from CVDs. CVD represents 31% of all deaths; moreover, heart attack and stroke are the leading cause of death from CVD [ 2 ].WHO also reported that around 55% of the adult population were physically inactive. This percentage likely increases among the prison population.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a growing interest in sex-dimorphism particularly for those disorders associated with metabolic perturbations. There is a sex-specificity in the risk of CVD [ 45 , 46 ] and lipid metabolism in obesity [ 43 , 47 ]. Such differences in disease risk are potentially reflected in metabolic profiles.…”
Section: Discussionmentioning
confidence: 99%
“…They include open social networks (e.g., Facebook, Linkedin, Twitter, Instagram) which have not been designed for health-related interactions, as well as intentionally designed social networks (e.g., PatientsLikeMe, Mumsnet, TreatmentAction Campaign, My Pro Ana) with an explicit interest in health and health behaviors [ 5 ]. Whether they are open or intentionally designed social networks, online communities are likely to increase knowledge about health and even influence the health status of people [ 5 , 6 , 7 , 8 ]. For example, it has been demonstrated that social ties in the virtual environment reduce risks of depression among the elderly and boosts their self-confidence [ 9 ].…”
Section: Introductionmentioning
confidence: 99%